Effects of isolation in older adults during pandemic: a review of the literature - Granda-Oblitas, Alexandra (2021)
Isolation as a restrictive measure during the SARS-COV-2 pandemic has generated negative effects on the population, especially on the health of older adults. A literature review was conducted using SCOPUS, Google Scholar, PubMed and Scielo databases published as of December 2019. For the results, the association of social isolation with COVID-19, physical consequences, psychological effects, neurodegenerative diseases, and assessment and management was made. The articles used provide information from a specific time period, so it is unknown what the long-term effects might be, and whether there is really a difference with the pre-pandemic health status. However, it is of utmost importance to establish measures to mitigate the effects both physically and mentally, that are adapted to the reality of each country.